Assessment of E-Learning Facilities and Personnels for Teaching Science in Osun State Senior Secondary Schools in Nigeria - Abanikannda, Mutahir Oluwafemi (Journal of Innovative Science Education, 2024)
The study assessed e-learning facilities and personnels for teaching science in senior schools in Osun State. The study is a descriptive study; a sample of 300 respondents from Oriade Local Government, Osogbo Local Government and Olorunda Local Government Area of Osun State formed the participants for the study. The instrument for data collections was inventory and check list and reliability level was 0.85. Data collected were analyzed using via percentage, frequency count, t-test and Person Product Moment Correction (PPMC). The findings of the study revealed that high cost of computer, fear of losing computer, monthly subscription for the internet usage, availability of some pornographic sites, underfunding from our government budgeting and irregular power supply were highest challenges encounter by science teachers in using E-learning facilities in Secondary Schools in Osun State. Study revealed that awareness campaign on the benefits of e-learning within and outside institution and employment of ICT skilled teachers are the measures to be adopted for the enhancement of the utilization of e-learning for teaching science. Hence, there is a positive and a significant relationship between e-learning utilization in teaching students and academic achievement in science. The following recommendation were made such as: employers of teachers should give sufficient technical skills to their employees on e-learning tools, ministry of education and local government education authority should provide computers, internet and other ICT tools and teachers training institutions like institutes of education, colleges of education, National Teachers Institutes and so on should make ICTs course compulsory for all the teachers under training.